A study on optimal parameter combinations for austempered ductile iron - Oktadinata, Herry; Purnama, Dewin; Hamzah, Rizal Nurdian; Apriyan, Agung Slamet (Jurnal Polimesin, 2024)
Nodular cast iron possesses a spherical graphite shape and exhibits mechanical properties closely resembling those of steel after heat treatment. The austempering method provides a means of enhancing the mechanical properties of nodular cast iron. This study aimed to investigate the optimal parameter combinations for Austempered Ductile Iron (ADI). The experiments involved varying the austenitization temperature and austempering time. Multiple tests were conducted to analyze the effects of austenitization temperature and tempering time on the microstructure, hardness, and impact toughness. The experimental samples were obtained from Y-block nodular cast iron austenitized at 850, 900, and 950°C for 90 min in an electric furnace. Subsequently, they were quenched in a salt bath at a temperature of 350°C and held for 60, 90, and 120 minutes before being cooled to room temperature. Mechanical tests and microstructure observations were performed on both the as-cast sample and after austempering. The microstructure was observed using an optical microscope before and after the etching. The research findings indicated that austempering increases the hardness and impact toughness of nodular cast iron. The highest hardness (46.8 HRC) was achieved from a parameter combination of an austenitization temperature of 850°C and an austempering time of 90 minutes. This particular sample also exhibited a relatively higher impact energy (3.8 J) compared to the others. The results of this study suggest that the austenitization temperature and tempering time exert an influence on the mechanical properties.